(untitled) (Research, Society and Development, 2021)
The State of Rio Grande do Sul has a prominent role in milk production nationwide and the southern region of the state stands out as one of the main dairy basins in the State. The objective of this study was to characterize the zootechnical and sanitary profile in 51 bovine herds in the microregion of Pelotas. From the information obtained through interviews, a database was built and a description of the data was obtained by indicating how the individuals in the group vary. In this study, the properties had a median of four residents (DI=3) and time spent in dairy farming of 20 years (DI=26), the total area was 40 ha (DI=57), and the area was exclusively dedicated to production. dairy (animal facilities and rest and grazing areas) of 23 ha (DI=32). The properties presented a median of 20 lactating cows (DI=26) and five dry cows (DI=7), the number of heifers from one year of age was nine (DI=16) and the number of heifers with less of one year was eight (DI=11), the total herd herd was 44 animals (DI=63). The effective of other species of domestic animals such as dogs, horses, chickens, swine, sheep and goats was evaluated. Medians of three dogs (DI=3), two horses (DI=1.75), 30 chickens (DI=30), three swine (DI=4), four sheep (DI=10) and five goats (DI=DI) were observed. =3). The results of this study indicate that there is great heterogeneity and low agricultural pluriactivity in the milk production process in southern Rio Grande do Sul, supported mainly by small properties, based on family labor and associated with the use of technologies such as artificial insemination and mechanical milking.